Do Marketing Events Matter to Capital Markets? Evidence from the Indonesian Telecommunications Industry - Zulfikar Fauzi; Hylman Jatmiko Nur Wicaksana; Intan Tamara Febrinzky; Faisal Akbar (Politeknik Mardira Indonesia, 2026)
This study aims to analyze capital market reactions to large-scale national event marketing in the telecommunications service industry in Indonesia. Event marketing is considered a form of non-financial information that may be reflected in stock price movements. This research employs a quantitative approach using an event study methodology, focusing on PT Telkom Indonesia Tbk (TLKM) and PT Indosat Ooredoo Hutchison Tbk (ISAT) over the period of 2022–2024. The data consist of daily stock prices (market price open) and event marketing dates obtained from official company sources and media reports. The analysis is conducted using a simple regression model with a dummy variable to distinguish between event days and non-event days within the observation window. The results indicate that event marketing does not have a significant effect on stock market price open. Furthermore, no significant differences are found between stock prices on event days and non-event days. These findings suggest that event marketing is not perceived as sufficiently strong information to influence capital market reactions in the short term. This study contributes to the literature by extending the understanding of the role of non-financial information in capital markets, particularly in the context of service industries in emerging economies.